Формування історичної спадщини парамілітарного руху у Галичині (наприкінці XIX – на початку XX ст.) - Нагірняк, А. Я. (Publishing House of Lviv Polytechnic National University, 2014)
Висвітлені основні здобутки формування української історичної спадщини з проблеми еволюції парамілітарних рухів Галичини кінця ХІХ – початку ХХ ст. в українські військові з’єднання. The paper highlights the main achievements of Ukrainian historiographical heritage from the point of view of the evolution of Galicia paramilitary movements of the late XIX – early XX century, the Ukrainian military units. The article highlights and analyzes the main stages of the study: 1) works of researchers of the interwar period in Western Ukraine and the diaspora historians, who laid the conceptual foundations of informative study of the entire Ukrainian national movement and political history and the history of Cossack riflemen paramilitary companies in particular; 2) The work of historians of the Soviet period; 3) The studies of Ukrainian historians who appeared in the late 80’s – early 90’s of XX century during the collapse of the Soviet Union when the history of paramilitary organizations was treated as a “white spot” and in terms of the existing Soviet system was forbidden to write about; 4) The works of historians of the period of independent Ukrainian were based on democratic methodological principles. Particular attention is drawn to the memorable leaflets, which were published in Western Ukraine, Canada and the U.S., which form two groups of works of civil and political activists ZUNR. Of the greatest importance to historians is the work of ZUNR leader K. Levytskyi who investigated the problems of national revival in the late XIX – early XX century and activities of socio-political organizations and paramilitary associations. The importance of the historical-journalistic publications, which mainly took the form of leaflet memories in the 20’s of the twentieth century was also emphasized. The role of contemporary Ukrainian newspapers, including significant place, which is occupied by the military – historical illustrated magazine “Chervona Kalyna Chronicles”, which came out in Lviv in 1929–1939 s. A lot of leaflet memories and biographies of participants liberation struggle 1914–1923 were published there.